Investigation and Optimization of Mechanical, Thermal and Tribological Properties of UHMWPE – Graphite Nanocomposites. (2018) - Sai Narendra Reddy, K.; Unnikrishnan, D.; Balachandran, Meera
Abstract: The objective of this study is to investigate the influence of nano-sized graphite on the mechanical, thermal and wear characteristics of Ultra High Molecular Weight Polyethylene (UHMWPE) - Graphite (Nano 27) nanocomposites. Mechanical, wear and thermal properties were analyzed for nanocomposites containing 0.5, 1, 1.5 and 2% graphite and compared with unfilled UHMWPE. The wear properties of the nanocomposites were modeled and optimized for nano-graphite content and process parameters viz. sliding velocity and load. Response surface methodology (RSM) was utilized for modeling and optimization for reducing the wear rate in the nanocomposites. The degree of wear and the worn surfaces were evaluated by Field Emission Scanning Electron Microscope (FESEM).